Mapping Motor Neuron Vulnerability in the Neuraxis of Male SOD1G93A Mice Reveals Widespread Loss of Androgen Receptor Occurring Early in Spinal Motor Neurons - McLeod, Victoria M.; Chiam, Mathew D. F.; Perera, Nirma D.; Lau, Chew L.; Boon, Wah Chin; Turner, Bradley J. (Frontiers in Endocrinology, 2022)
Sex steroid hormones have been implicated as disease modifiers in the neurodegenerative disorder amyotrophic lateral sclerosis (ALS). Androgens, signalling via the androgen receptor (AR), predominate in males, and have widespread actions in the periphery and the central nervous system (CNS). AR translocates to the cell nucleus when activated upon binding androgens, whereby it regulates transcription of target genes via the classical genomic signalling pathway. We previously reported that AR protein is decreased in the lumbar spinal cord tissue of symptomatic male SOD1G93A mice. Here, we further explored the changes in AR within motor neurons (MN) of the CNS, assessing their nuclear AR content and propensity to degenerate by endstage disease in male SOD1G93A mice. We observed that almost all motor neuron populations had undergone significant loss in nuclear AR SOD1G93A mice. Interestingly, loss of nuclear AR was evident in lumbar spinal MNs as early as pre-symptomatic age 60 days. Several MN populations with high AR content were identified which did not degenerate in SOD1G93A mice. These included the brainstem ambiguus and vagus nuclei, and the sexually dimorphic spinal MNs: cremaster, dorsolateral nucleus (DLN) and spinal nucleus of bulbocavernosus (SNB). In conclusion, we demonstrate that AR loss directly associates with MN vulnerability and disease progression in the SOD1G93A mouse model of ALS.